PENGARUH KUALITAS PELAYANAN M-BANKING, BRAND IMAGE, CELEBRITY ENDORSEMENT TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL MEDIASI - Seraya, I Gusti Putu Fajar Pala; Mahyuni, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023, 2023)
The tight selection of the banking world today makes customers more critical to make choices. In order to create customer satisfaction which is an expectation in the use of services and the use of banking facilities, banks through customer satisfaction continue to strive for customer loyalty. This study aims to examine the effect of M-Banking Service Quality, Brand Image, Celebrity Endorsement on Customer Loyalty with Customer Satisfaction as a Mediating Variable. This research was conducted at BRI Tabanan Branch Office. The research population is all customers who make transactions at BRI Tabanan Branch.  Structural equation model is used as a data analysis technique in this paper. This study concluded that